Biohybrid nanocomposite production and characterization by RSM investigation of thermal decomposition kinetics with ANN - Aydogmus, Ercan (Springer Heidelberg, 2022)
In this research, a biohybrid nanocomposite (BHNC) reinforced with graphene (GF), multi-walled carbon nanotube (MWCNT), silicon carbide (SiC), and modified palm oil (MPO) has been synthesized. Both the experimental work plan and the optimum component amounts of BHNC have been determined according to the response surface methodology (RSM). Density, hardness, thermal conductivity coefficient, thermal stability, scanning electron microscope (SEM), and Fourier transform infrared spectroscopy (FTIR) of BHNC have been investigated by characterization processes. Activation energy values calculated in BHNC's thermal decomposition experiments are simulated using artificial neural networks (ANN). Also, new experimental systems have been improved for both MPO synthesis and the thermal decomposition of BHNC. According to the results obtained, as the mass of nanoparticles and MPO in the BHNC composition increases, the density, Shore D hardness, and thermal conductivity coefficient of this composite also raise. However, it has been determined that the effect of each nanoparticle on BHNC is different. When the most dominant properties on BHNC have been discussed, SiC, Shore D hardness, and MWCNT density affected the GF thermal conductivity coefficient. MPO is also found to significantly increase the activation energy of BHNC. Based on data obtained during thermal decomposition, BHNC's activation energy values have been found 133.978 kJ/mol (Flynn-Wall-Ozawa), 131.245 kJ/mol (Kissinger), and 127.694 (Coats-Redfern) for experiment 11.
Keywords: Biohybrid nanocomposite; Characterization; Thermal decomposition; RSM; ANN